2021
DOI: 10.1039/d1tb01025e
|View full text |Cite
|
Sign up to set email alerts
|

A novel self-targeting theranostic nanoplatform for photoacoustic imaging-monitored and enhanced chemo-sonodynamic therapy

Abstract: Sonodynamic therapy has attracted wide attention as a noninvasive therapy due to deep tissue penetration. However, the majority of sonosensitizers often suffer from poor physiological stability, rapid blood clearance and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…51 Intriguingly, HeLa cells pretreated with the excessive free FA as a kind of folate receptor blocker remarkably suppressed the cellular uptake of PFP-NBD, implying that PFP might selectively distinguish tumor cells via self-targeting folate receptors on account of the selective binding affinity of PEM ligands on PFP's surface toward the folate receptors on the tumor cell membrane surface. 17 To further evidence the abovementioned speculation, the cellular uptake of PFP-NBD was also investigated with HeLa, A549, and L02 cells. As depicted in Figure 4C, an obvious result revealed that fluorescence signals from PFP-NBD within HeLa cells were far stronger compared with those within A549 or L02 cells.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…51 Intriguingly, HeLa cells pretreated with the excessive free FA as a kind of folate receptor blocker remarkably suppressed the cellular uptake of PFP-NBD, implying that PFP might selectively distinguish tumor cells via self-targeting folate receptors on account of the selective binding affinity of PEM ligands on PFP's surface toward the folate receptors on the tumor cell membrane surface. 17 To further evidence the abovementioned speculation, the cellular uptake of PFP-NBD was also investigated with HeLa, A549, and L02 cells. As depicted in Figure 4C, an obvious result revealed that fluorescence signals from PFP-NBD within HeLa cells were far stronger compared with those within A549 or L02 cells.…”
Section: 4mentioning
confidence: 99%
“…These phenomena combined with our previous report substantially confirmed that PFP possessed outstanding self-targeting capacity since the binding affinity of PEM ligands on PFP's surface toward folate receptors on the HeLa cell membrane surface could lead to an effective cellular uptake. 17 In view of consideration that both the normal tissue and tumor tissue possess the obvious acid difference. To accurately simulate the neutral physiological environment and moderate the acidic tumor microenvironment, respectively, HeLa cells were further incubated with PFP-NBD at pH 7.4 and 6.5, respectively.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al assembled the sonosensitizer ICG and TPGS-PEM prodrug (D-α-tocopheryl polyethylene 1000 succinate (TPGS) modified by pemetrexed (PEM)) into dual-mode imaging and active targeting TPGS-PEM-ICG nanoplatform (TPI). 140 The FL signal of HeLa tumour-bearing mice was the highest at 6 h and lasted until 24 h after TPI injection through the tail vein. The peak PA signal in the tumour area reached the peak 6 h after injection.…”
Section: Sonosensitizers With Various Imaging Functionsmentioning
confidence: 96%
“…Self-assembly GdHF-NDs, Mn (III)-HFs, Ce6-PTX@IR783, APHB NPs, TPI, ABS-FA, RB-MBs [30,35,43,94,101,131,140] Thermal decomposition Fe-TiO 2 NDs [41] Encapsulation DOX/Mn-TPPS@RBCs, GMCDS-FA@CMC, CPDP NPs, RBC-HPBs/HMME/PFH, FHMP NPs, (QD@P) Rs, MG@P NPs, IHG@P NPs, LIP3, OI_NPs, OIX_NP, AIMP NPs, IR780-NDs, FA-OINPs, mTiO 2 @PPYs, F3-PLGA@MB/Gd NPs, MnTTP-HSAs, PIO_NPs gene is inserted directly into the cell's DNA, the imaging is generated only in the living cell and can retain accurate imaging for a long time as the cell divides and is passed on to daughter cells. 163,164 Various molecular imaging modalities, including FLI, PAI and MRI, could be used for reporter gene imaging for gene activity monitoring, cell tracing and gene therapy monitoring.…”
Section: Synthesis Strategies Sonosensitizers Refsmentioning
confidence: 99%